1995
DOI: 10.1002/ajmg.1320580407
|View full text |Cite
|
Sign up to set email alerts
|

Use of decision analysis to evaluate patients' choices of diagnostic prenatal test

Abstract: Women with a family history of a chromosomal or genetic abnormality must weigh several factors in choosing between amniocentesis and chorionic villus sampling. We compared the prenatal test choices of three such women with those of decision analytic models that incorporated their preferences. Patient preferences were assessed using visual linear rating scales. Threshold analysis was used to determine preference ranges, and stochastic sensitivity analysis to provide confidence levels, for each choice of test. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Studies on the freedom or voluntary nature of women's participation in prenatal screening have yielded conflicting results. On the one hand, Verp and Heckerling 28 argued that every woman has a unique decisionmaking process that influences her choice and receptivity to prenatal screening, and Sjogren 20 found that the most women sought autonomy regarding the use of reproductive technology and did not want authorities to make their decisions. On the other hand, Santalahti 14 interviewed women in different phases of prenatal screening and asked them to describe their decision-making processes.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the freedom or voluntary nature of women's participation in prenatal screening have yielded conflicting results. On the one hand, Verp and Heckerling 28 argued that every woman has a unique decisionmaking process that influences her choice and receptivity to prenatal screening, and Sjogren 20 found that the most women sought autonomy regarding the use of reproductive technology and did not want authorities to make their decisions. On the other hand, Santalahti 14 interviewed women in different phases of prenatal screening and asked them to describe their decision-making processes.…”
Section: Resultsmentioning
confidence: 99%
“…Because diagnosis is available sooner after the test is performed and earlier in pregnancy with CVS than with genetic amniocentesis (GA), a potential advantage of CVS is a reduction in the duration of anxiety and stress for reproductive couples. An additional potential health-related quality-of-life (HRQL) advantage of CVS is the ability to terminate the pregnancy during the first trimester (with a decreased risk of complications to the woman) prior to fetal movement or public awareness (Blumberg et al, Fava et al, 1982;Caccia et al, 1991;Robinson et al, 1988;Heckerling and Verp, 1991, 1994a, 1994b, 1998Heckerling et al, 1994;Verp and Heckerling, 1995;Kuppermann et al, 1997Kuppermann et al, , 1999aKuppermann et al, , 1999bHarris et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Heckerling and Verp (see also Heckerling and colleagues and Verp and Heckerling) present a similar decision model that focuses on the decision of whether or not to undergo prenatal diagnosis and the choice of modality of testing [38][39][40][41][42]. Their model omits diagnostic inaccuracy and subsequent reproductive behavior.…”
Section: Obtaining Preference Scores For Health States Associated Witmentioning
confidence: 99%
“…Wonderling indicates that although the expected utility of GA exceeds that of CVS (overall considering both process and chronic outcome or when considering chronic outcome alone), with respect to process (temporary health states) alone, the expected utility of CVS exceeds that of GA [30]. Heckerling and Verp indicate that the expected utility of GA exceeds that of CVS which in turn exceeds that of no testing, but again differences were small [38,42]. Heckerling and Verp indicate that the expected utility of GA exceeds that of CVS which in turn exceeds that of no testing, but again differences were small [38,42].…”
Section: Estimates Of the Expected Utility Of Prenatal Diagnosismentioning
confidence: 99%